Development of Cascara Tisane with The Addition of Dried Pineapple (Ananas sativus) and Rosella Flower (Hibiscus sabdariffa) - Dinda Wardhany; Mohammad Affan Fajar Falah (Agroindustrial Journal, 2023)
Coffee cherry skin, a form of coffee production waste that accounts for up to 60% of the total yield, contains natural antioxidants that have the potential to become functional foods. Cascara Tisane is a brewed beverage derived from dried coffee cherry skin. Adding other ingredients to this product can help increase consumer acceptance in Indonesia. In this study, the additional ingredients used were dried pineapple and rosella flowers. To determine the effect of adding these ingredients, it is necessary to identify the drying temperature and chemical and organoleptic characteristics to produce Cascara Tisane products according to the Indonesian National Standard (SNI). The research consisted of two stages, namely (1) the identification of the drying temperature of coffee cherry skin and (2) the formulation of the addition of dried pineapple and rosella. The drying temperatures used were 45 oC, 50 oC, 55 oC, and 60 oC. The sample formulation consists of four levels, namely code 126 (75% coffee cherry skin, 15% dried pineapple, 10% rosella): 216 (65% coffee cherry skin, 20% dried pineapple, 15% rosella); and 616 (55% coffee cherry skin, 25% dried pineapple, 20% rosella). Chemical characteristics analysis was conducted on moisture and ash contents, as well as antioxidant activity. Furthermore, a hedonic test was used to evaluate cascara tisane products' organoleptic characteristics (aroma, taste, color, and aftertaste) with a 5-point hedonic scale. The results showed the optimum drying temperature of coffee cherry skin at 45 oC, with the most preferred formula being formula 616.